Molecular Docking Approach to Curcumin Compounds and Its Derivatives as Anticancer Agents: A Literature Review - Rani Putri Luthfiani; Nadya Nasywa Saputri; Saeful Amin (Journal of Engineering Science and Technology Management, 2026)
Cancer remains a major global health challenge, with increasing incidence and mortality rates. This study aims to regularly review the potential of curcumin and its derivatives as anticancer agents using molecular docking approaches. A Systematic Literature Review (SLR) was conducted, analyzing ten original articles published between 2020 and 2025 from PubMed and Google Scholar. The population encompassed all full-text studies on molecular docking of curcumin and its derivatives against cancer protein targets, with purposive sampling based on inclusion and exclusion criteria. Data were extracted on ligands, protein targets, docking software, validation parameters, and binding energies, then analyzed using narrative synthesis and comparative methods. The results show that curcumin and its derivatives interact with multiple cancer-related proteins, such as EGFR, HER2, CDK2, and androgen receptors, with derivatives exhibiting more stable binding energies (−6 to −9 kcal/mol) than natural curcumin. These findings indicate that curcumin derivatives have higher anticancer activity and overcome bioavailability limitations. The conclusion highlights the need for standardized molecular docking protocols and integration with biological assays to support clinical development of curcumin-based therapies.